2013
DOI: 10.1590/s0102-77862013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Análise e estimativa dos componentes do balanço de energia em ecossistema de manguezal amazônico

Abstract: RESUMO O objetivo do presente trabalho é analisar a importância dos mapas mentais na percepção ambiental de alunos do 6º ano do Ensino de Ciências, quanto ao ecossistema manguezal. Para tanto, foi solicitado aos alunos que representassem o manguezal através de desenhos (mapas mentais), no intuito de avaliar o nível de percepção ambiental e de que maneira o ecossistema manguezal é visto por esses discentes. A análise foi feita através de categorização temática, permitindo a sistematização e interpretação das in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…According to climatic studies by Pereira and Rodrigues ( 2013 ) and Silva Junior et al ( 2006 ), in the mangrove ecosystem of Bragança (State of Pará), the months of February, March, and April are the rainiest, with March being the one with the highest accumulated precipitation, with values above 700 mm for the years from 2001 to 2003.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to climatic studies by Pereira and Rodrigues ( 2013 ) and Silva Junior et al ( 2006 ), in the mangrove ecosystem of Bragança (State of Pará), the months of February, March, and April are the rainiest, with March being the one with the highest accumulated precipitation, with values above 700 mm for the years from 2001 to 2003.…”
Section: Resultsmentioning
confidence: 99%
“…3B). Pereira and Rodrigues (2013), analyzing the energy partition in the mangrove ecosystem on the coast of Pará, found that in the wet season, the maximum value of H occurred in January at 1:00 pm with 274.7 W m −2 . On the other hand, the maximum LE observed occurred in May at 11:00 am with 374.7 W m −2 .…”
Section: Studies Of Global Liquid Radiation and Energy Fluxes For The Wet And Dry Seasonsmentioning
confidence: 99%
See 1 more Smart Citation